ANALGESIC POTENTIAL OF VITEX TRIFOLIA LINN (VERBANEACAE). - LA, Kulkarni (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Acetic acid induced writhing test in mice and Tail immersion method in rats were employed to study the analgesic potential of Vitex trifolia Linn. (Verbaneaceae). The no of writhes were significantly reduced in acetic acid induced writhing test at lowest (200mg) & at the highest (400mg) dose levels whereas increased tail immersion time was observed in tail immersion method in rats at highest dose (400mg) levels. The data concluded that the Vitex trifolia Linn. possess the both central and peripheral analgesic potential. Â  Keywords: Acetic acid, Writhing, Tail immersion, Vitex trifolia Linn, Verbaneaceae